Hybrid process for bio-hydrogen and methane production from hydrogenic effluent : a mini review - Umarin Jomnonkhaow; Sureewan Sittijunda; Alissara Reungsang (Penerbit Universiti Kebangsaan Malaysia, 2021)
Hydrogenic effluent is the effluent from the bio-hydrogen production process via dark fermentation. It mainly consists of volatile fatty acids, residual sugars, and organic solid residues with a high chemical oxygen demand (COD), which prohibits direct discharge to the environment. Therefore, a post-process after dark fermentation to utilize the organic substances in the hydrogenic effluent is needed to complete the organic conversion and reduce the COD load. This review discussed the use of organic substances in the hydrogenic effluent to produce bioenergy, including bio-hydrogen, through photo fermentation and microbial electrolysis cells, and to produce methane by anaerobic digestion. Furthermore, the advantages and disadvantages of using hydrogenic effluent to generate bio-hydrogen and methane and the challenges and future perspectives on utilizing the hydrogenic effluent are discussed.